Oportunidades e desafios para lidar com as barreiras à adoção de práticas de green supply chain management: guidelines à luz de um estudo de múltiplos casos no Brasil - Jabbour, Ana Beatriz Lopes de Sousa [UNESP]; Souza, Caroline Lombardi de [UNESP] (Universidade Federal de São Carlos, 2015)
This article aims to discuss how leading companies of the automotive battery industry installed in Brazil are dealing with barriers to the adoption of green supply chain management (GSCM) practices. From these discussions, we list the opportunities and challenges to the automotive battery sector in incorporating GSCM actions. We conducted a multiple-case study with the top five companies in this sector. The highlight factors are “organizational values” and “human resources” for internal barriers, and “suppliers” and “consumers” for external barriers.

Este artigo tem como objetivo apresentar e discutir como as principais empresas montadoras do setor de baterias automotivas instaladas no Brasil estão lidando com as barreiras à adoção de práticas de green supply chain management (GSCM). A partir dessas discussões, elencam-se oportunidade e desafios ao setor de baterias automotivas a fim de considerarem ações de GSCM. Foi realizado um estudo de múltiplos casos com as 5 principais empresas desse setor. Os fatores de destaque para as barreiras internas são “valores e fatores organizacionais” e “recursos humanos” e, para as externas, são “fornecedores” e “consumidores”.
Opportunities and challenges for dealing with barriers to the adoption of green supply chain management practices: guidelines based on multiple-case studies in Brazil
Keywords: Green supply chain management; Barriers; Opportunities; Challenges; Automotive battery companies; Green supply chain management; Barreiras; Oportunidades; Desafios; Empresas de baterias automotivas